Thoracoscopic lobectomy for lung cancer in challenging cases: technical aspects - Curcio, Carlo; Amore, Dario; Casazza, Dino; Saglia, Alessandro; Imitazione, Pasquale; Izzo, Alessandro; Rispoli, Marco; Nespoli, Moana Rossella (Current Challenges in Thoracic Surgery; Vol 1 (December 2019): Current Challenges in Thoracic Surgery, 2019)
Over the last years, in the management of patients with early stage non-small cell lung cancer (NSCLC), video-assisted thoracoscopic surgery (VATS) lobectomy has been considered an optimal alternative to conventional thoracotomy and several studies have demonstrated his superiority over open lobectomy in terms of peri-operative outcomes. Nowadays, increased experience and technological advancements in minimally invasive thoracic surgery are leading surgeons to deal with more complex cases and some conditions as chest wall involvement or previous cardio-thoracic surgery are no longer considered an absolute contraindication to VATS lobectomy. Advanced thoracoscopic skills are required to perform N1 nodal dissection that can be challenging in presence of bulky lymphadenopathy or extracapsular invasion by metastatic lymph nodes.